Sistem Mitigasi Terintegrasi Tanggap Darurat Kebakaran Berbasis Internet of Things - Mochammad Fadillah Putra; Sutisna; Firmansyah M S Nursuwars; Andri Ulus Rahayu (Department of Electrical Engineering, UNJANI, 2022)
Fire is an event that most often effects both urban and rurals areas. This incident is very dangerous beacause it can cause loss and loss life. Ingeneral, these fire cannot be predicted when and where they will occur. The bigger the fire, the bigger the impact, to minimize the risk of fire, a tool is needed that can provide early fire information that can be monitored so that fires can be handled quickly. With the application of internet of things technology using an ESP32 board via internet network and assisted by fire sensors, gas sensors, and temperature sensors, they are able to detect potential fires early. The data displayed is in the form of fire status, gas leaks, and temperature monitoring So in this study, a tool is made that is able to make it easier to provide fire information with the average time needed for 15.81 seconds and the system is able to provide accurate location because the location set is the identity or address of each of the sensor devices. and gateways.